HIGH-ORDER FINITE DIFFERENCE METHOD APPLIED TO THE SOLUTION OF THE THREE-DIMENSIONAL HEAT TRANSFER EQUATION AND TO THE STUDY OF HEAT EXCHANGERS - Campos, M. D.; Romão, E. C. (Revista de Engenharia Térmica, 2014)
Numerical experiments for four test problems are carried out to demonstrate the performance of the present method and to compare it with the others classical methods. The numerical solutions obtained are compared with the analytical solution as well as the results by other numerical schemes with emphasis on the application involving heat exchange in a rectangular channel. It can be easily seen that the proposed method is simple to implement and very efficient.